The handbook of asset/liability management : state-of-the-art investment strategies, risk controls, and regulatory requirements - Fabozzi, Frank J.; Konishi, Atsuo (Chicago, Ill. : Irwin Professional Pub., 1996)
Provides insights into the key issues facing financial experts, including: benefits from risk management; asset securitization; measuring interest rate and yield curve risk; using OAS to implement value at risk balance sheet management; hedging with derivatives; implementing controls for managing derivative positions; FASB 15 and Thrift Bulletin 13 considerations in managing a portofolio; and the implications of risk-based guidelines for managing an MBS portofolio.
Rev. ed. of: Asset/liability management. c1991.
Includes bibliographical references and index.
nif 23/04/13
Loans
Keywords: Asset-liability management